2008
DOI: 10.1002/jmv.21198
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of high‐risk human papillomavirus genotypes persistence and risk of residual or recurrent cervical disease after surgical treatment

Abstract: The evidence on genotype-specific risk in women infected with human papillomavirus (HPV) with normal cytology and the importance of the distinction of high-risk (HR)-HPV genotypes in the management of low-grade lesions suggest that the distinction of HR-HPV genotypes has the potential to improve the follow-up of patients treated for high-grade cervical lesions. The aims of this study were to define the persistence of the different HR-HPV in the follow-up of surgical treated women, to detect the changes of geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
37
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
7
37
1
3
Order By: Relevance
“…However, we found that high-risk HPV infection was more common in patients with VAIN III than those with VAIN I-II, showing linear by linear association like a previous study where positivity to high-risk HPV infection has been reported to be significantly higher in patient with relapse to VAIN after laser vaporization [25]. Moreover, high-risk HPV infection has been shown to increase the rate of recurrence in CIN [26], and to contribute to the development of multifocal lesions known to be a significant risk factor for VAIN [16]. It means that high-risk HPV infection may be associated with advanced-disease of VAIN and it may be a possible risk factor for recurrence in patients treated with laser vaporization due to VAIN.…”
Section: Discussioncontrasting
confidence: 42%
“…However, we found that high-risk HPV infection was more common in patients with VAIN III than those with VAIN I-II, showing linear by linear association like a previous study where positivity to high-risk HPV infection has been reported to be significantly higher in patient with relapse to VAIN after laser vaporization [25]. Moreover, high-risk HPV infection has been shown to increase the rate of recurrence in CIN [26], and to contribute to the development of multifocal lesions known to be a significant risk factor for VAIN [16]. It means that high-risk HPV infection may be associated with advanced-disease of VAIN and it may be a possible risk factor for recurrence in patients treated with laser vaporization due to VAIN.…”
Section: Discussioncontrasting
confidence: 42%
“…Secondly, we can also exclude that positive HPV test results at the initial follow-up visit reflected the transient presence of lowrisk virus types unrelated to the treated lesion [13]. As shown in Table 2, transient post-treatment positive test results were generally caused by the same virus type that infected cancer cells -and not by the presence of different virus types in the cervical/vaginal environment.…”
Section: Discussionmentioning
confidence: 97%
“…HPV genotyping is important for most of the major medical indications of HPV testing. For example, genotyping of HPV has been shown to be an accurate indicator of treatment failure in follow-up after treatment for cervical dysplasia (1,22). In cervical screening, HPV genotyping better identifies women at high risk of dysplasia than does a nongenotyping HPV test (6), and monitoring of the types that are associated with the highest risk for cancer is particularly important (3,22).…”
mentioning
confidence: 99%
“…For example, genotyping of HPV has been shown to be an accurate indicator of treatment failure in follow-up after treatment for cervical dysplasia (1,22). In cervical screening, HPV genotyping better identifies women at high risk of dysplasia than does a nongenotyping HPV test (6), and monitoring of the types that are associated with the highest risk for cancer is particularly important (3,22). The monitoring of the effect of HPV vaccination requires adequate HPV genotyping to evaluate whether vaccine HPV types disappear from the population and how the prevalence of nonvaccine types is affected (8).…”
mentioning
confidence: 99%